O contexto do desenvolvimento de nadadores medalhistas olímpicos brasileiros - Renato Melo Ferreira (2010)
Expertise involves possessing vast knowledge about many factors in a particular field, for example, in sports. Various models evaluate the factors that influence these exceptional people, from the perspective of the ambient. The aim of the study was to evaluate the environment in which the expert developed; specifically those of Olympic medal-winning Brazilian swimmers. The study is based on personal interviews with the swimmers, as well as a thorough analysis of the interview. The study also explores the differences between those athletes who trained in the USA, and those that trained in Brazil. Eight Brazilian swimmers, all of whom had won at least one Olympic medal, were interviewed. The interviews were recorded and transcribed, and then analyzed by three leading experts in the field. The results of the interviews indicated that there were 473 MU.s (Meaning Units . MU.s), where the following classifications were set: Begging to have a swimming career, influential people, quality characteristics in their coach, support and recognition, major differences between being trained in the USA vs. Brail, deliberated practices and resources. Having family support, a specialized coach, deliberated practices and fundamental resources were the factors that helped those swimmers. The major differences between Brazil and USA were the availability of the studies done on the high-level practice programs, the high quality of the swimmers on the team, the accessibility of technology, etc. In conclusion, the differences in realities indicate there is not a rigid pattern needed for the development of excellence. Also important to note is that the training in the USA was of a higher quality, although two of the athletes had success training in Brazil alone